PENINGKATAN KERJASAMA ANTAR UMKM DI KECAMATAN PEDURUNGAN KOTA SEMARANG MELALUI PELATIHAN SOSIAL MADIA MARKETING - Prabowo, Catur; Fahlefi, Diva Riza; Pelupessy, Ig. Henri; Harminingtyas, Rudika (STIE Pelita Nusantara, 2025)
Pedurungaan sub-district, which consists of many sub-districts and community units (RW), has hundreds of MSMEs that have been established, both pioneered by young people or housewives and many have a semi-modern system involving digital technology in marketing their products or services. The MSMEs were given training on improving the use of social media marketing and how to build a communication network in order to form a cooperation ecosystem between MSMEs to mutually strengthen the quality of their products or services by establishing cooperation between MSMEs. They feel that what they have done so far has not been optimal because they do not know what to do with the progress of the communication network cooperation. With this training, they open their hearts and minds to develop their business with the knowledge received during this training, namely marketing through social media marketing. This training is very helpful for MSMEs in trying to increase sales of their products so that they can cover their operational costs and can get decent profits and do not need to worry about sluggish sales due to limited sales capabilities and existing distribution networks and to increase sales and consumer trust we also conduct training on how to build a network of cooperation between MSMEs. It is expected that participants can continue to improve their business and use the right social media so that the business they run can grow.